Tobacco smoking among school adolescents in Northern Sabah - Swe; Than Myint; Mon Mon Yee (Bangladesh Journals OnLine (BanglaJOL), 2016)
Tobacco smoking in adolescent age group has become a major public health concern as it is one of the major risk factors for non-communicable diseases leading to burden of adverse health effects in their later life. Those who start smoking tobacco at an early age are more likely to develop nicotine addiction and continue smoking throughout their adulthood. The general objective of the study was to determine the prevalence of tobacco smoking, their initiation and perception towards tobacco smoking among school adolescents in Kudat District, Sabah State, Malaysia. It was a school based cross sectional descriptive study which employed a two-staged stratified random sampling method and used self-administered structured questionnaire for data collection. A total of 257 students aged between 15 to 19 years old from two upper secondary schools participated in the study. This study revealed that (26.6%) were ever smokers and (8.6%) were current smokers. The earliest age of started smoking was 7 years old and 9 years old among male and female ever smokers respectively. Majority of the respondents perceived that smoking was a bad habit which would cause environmental pollution and harmful effects on health. The most common reasons to start smoking among ever smokers were peer pressures, curiosity and experimenting and to relieve the feeling of pressured and stress. Among the current smokers, 86.4%had ever attempted to quit smoking but they failed to stop smoking because they thought smoking could give feeling pleasure (50%), relieve their anxiety or craving (27.3%) and because of peer pressures (22.7%). The findings suggested that although tobacco smoking prevalence among school adolescents in Kudat was comparatively lower than that of national prevalence reported by GYTS, there is still need for early interventions with holistic approach to prevent them from initiation and to help them for cessation of tobacco smoking.